O financiamento da educação superior : uma análise do PNE 2001-2010 - Bechi, Diego (2013)
This research has like main objective understand the process of financing of higher education in the context of the National Education Plan (Law No 10.172/2001). During the investigative practice, starts from the presupposition that the construction and implementation of public policies are conditioned to the logic of financing established by the state. In view of this premise, we attempt to explore the issues relevant of the following question: what is and how they have historically constituted the intrinsic logic of financing to the elaboration, approval and materialization of the Education Plan, in respect to higher education? To answer this question, the research is structured around three chapters. In the first, takes as object of the study the funding of higher education on the process of preparation and approval of the Plan, emphasizing its nature, their protagonists, the different political positions and the interference of multilateral organizations. During this research, we search to understand the origin and purposes of the changes established in the national political-economic scenario from the 1990s, in order to explain how and in what dimension the global neoliberal policies have influenced the funding policies and management of higher education in Brazil. The subsequent chapter explores the logic of the intrinsic financing to the materialization process of the propositions relating to this level of education. In general, analyzes critically the way how it was structured and organized the public financing in the "Decade of Education" and in what dimension it contributed to fulfill the goals expressed in the law n º 10.172/2001. Finally, the third chapter presents different estimates of public investment (direct and indirect) in higher education and the origin of the resources of public and private institutions. Through this investigative process, of critical-reconstructive character, wants to advance in studies and researches in the field of educational policies, especially with regard to the National Education Plan, understood as a state policy, to contribute to the improvement of higher education in Brazil